2014
DOI: 10.1177/0741088314537599
|View full text |Cite
|
Sign up to set email alerts
|

Situating Transnational Genre Knowledge

Abstract: Scholars have recently begun to conceive of literacy practices as drawing from resources that are simultaneously situated and extracontextual. In particular, studies of transnational literacy affirm the importance of both locality and movement in literacy studies. Continuing this inquiry into the situated and dispersed nature of transnational literacy, the author investigates the distinct effects that shuttling between national contexts have on the accumulation and use of genre knowledge. Specifically, through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The current study revealed that the time abroad was found to develop a variety of academic skills which ATCKs could benefit from during their later studies, as well as in their jobs later on. This is an important finding because not much is understood about (A)TCKs academic competencies (Rounsaville, 2014). The findings indicated that due to having such competencies, ATCKs were given projects and positions in their organization that require not only cross-cultural skills, but also for example, good presentation skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study revealed that the time abroad was found to develop a variety of academic skills which ATCKs could benefit from during their later studies, as well as in their jobs later on. This is an important finding because not much is understood about (A)TCKs academic competencies (Rounsaville, 2014). The findings indicated that due to having such competencies, ATCKs were given projects and positions in their organization that require not only cross-cultural skills, but also for example, good presentation skills.…”
Section: Discussionmentioning
confidence: 99%
“…While most research has examined the experiences of TCKs abroad, the number of studies on their adulthood experiences has been gradually increasing. Initial studies have examined ATCKs' cultural identity (Greenholtz and Kim, 2009;Moore and Barker, 2012;Rounsaville, 2014;Walters and Auton-Cuff, 2009), insecurity of identity (Cranston, 2017) and cultural homelessness and identity (Hoersting and Jenkins, 2011). The well-being of ATCKs has been analyzed from perspectives such as their life satisfaction (Mosanya and Kwiatkowska, 2021), depression, anxiety and stress (Davis et al, 2010(Davis et al, , 2013, levels of prejudice (Melles and Schwartz, 2013) and loss and grief experiences (Gilbert, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following those previous studies, the linguistic realization in each language was also compared, focusing on verb tense and voice used in each abstract. For research on genre knowledge development, this study used the second instrument of an interview, following Rounsaville (2014) and Suherdi et al (2021). The interview was undertaken to explore the acquisition of genre knowledge through different levels of study, i.e., master's and doctoral degrees.…”
Section: Methodsmentioning
confidence: 99%
“…The findings indicated that students make significant gains in their writing over the course. Rounsaville's (2014) study, however, focuses on a case study of how one student's distinctly transnational genre knowledge developed in response to a series of relocations between Italy and the United States. The study found that the student's literacy history reveals the particularly transnational character of applying prior genre knowledge within new writing situations.…”
Section: Genre Knowledge Developmentmentioning
confidence: 99%
See 1 more Smart Citation